Penerapan Metode Diskusi Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Fiqih Kelas VII Madrasah Tsnawiyah Diponegoro Sumberjo Kandat Kediri - Siti Nursalimah (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2021)
Education in Indonesia is expected to prepare learners to become citizens who have a strong and contentious commitment to improve knowledge, intelligence, skills, morals, and develop skills, master the skills and fundamentals of technological science that build social integerity and civilize and realize national character. This research is descriptive qualitative research with a type of Classroom Action Research research conducted to improve students' learning outcomes by the application of discussion learning methods. The result of this study is that the application of Discussion Methods applied in the learning of Students of Class VII MTs Diponegoro Sumberjo Kandat can improve student learning outcomes. This is indicated by the percentage of students completing from cycle I by 54.54% in cycle II to 72.72%. Based on research the completion of class VII student learning is the highest increase in grades in cycle I to cycle II, from 85 to 90. There is an impact of the application of discussion methods during the learning process, namely the increasing activeness of students in their participation to participate in Fiqh lessons.